A case for a philosophical history of psychology: an interview with Saulo de Freitas Araujo at the centenary of the death of Wilhelm Wundt (1832–1920) - Fierro, Catriel; Araújo, Saulo de Freitas (Human Arenas, 2021)
On the occasion of the centenary of Wilhelm Wundt’s death (1832–1920), we had a conversation with Saulo de Freitas Araujo on the works and influence of the German author. After a brief introduction, the conversation begins with a reflection on the aims and objectives of Araujo’s work on the history and philosophy of Wundt’s psychology. A philosophical approach to the history of science and of psychology is then described. After considering the social and intellectual context of the revival of Wundt scholarship during the 1970s, Wundt’s philosophical and psychological project is discussed. The conversation ends with general reflections on Wundt’s legacy to recent and contemporary psychology.